2021
DOI: 10.1080/02673843.2021.1931376
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mentalization and borderline personality features in adolescents: mediating role of emotion regulation

Abstract: Dysfunctions in both emotion regulation and mentalization capacity might be reasons behind borderline personality features. This study investigated the mediating role of emotion regulation between mentalization and borderline personality features in adolescents. We recruited 218 adolescents (mean of age = 16.45 ± 1.01 years old, 62.0% girls) based on convenience sampling from high school students. We evaluated mentalization using reflective functioning questionnaire (RFQ), emotion regulation with difficulties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…Both rumination and worry can be conceptualized as maladaptive emotion regulation forms as they can show positive relationships with adverse outcomes of mental health [24,25]. Therefore, the co-occurrence of high levels of rumination, worry and mentalization difficulties is in accordance with those previous findings which showed positive correlations between difficulties in emotion regulation, maladaptive emotion regulation strategies and impairments in reflective functioning [2,[10][11][12][13][14]. The positive correlations between these variables might be accounted for the overlap between the items of the RFQ-R-7 and general emotion regulation difficulties (e.g., the item of "People's thoughts are a mystery to me"), whereas other items of the RFQ-R-7 show similar characteristics to rumination and worry (e.g., the item of "Strong feelings often cloud my thinking").…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Both rumination and worry can be conceptualized as maladaptive emotion regulation forms as they can show positive relationships with adverse outcomes of mental health [24,25]. Therefore, the co-occurrence of high levels of rumination, worry and mentalization difficulties is in accordance with those previous findings which showed positive correlations between difficulties in emotion regulation, maladaptive emotion regulation strategies and impairments in reflective functioning [2,[10][11][12][13][14]. The positive correlations between these variables might be accounted for the overlap between the items of the RFQ-R-7 and general emotion regulation difficulties (e.g., the item of "People's thoughts are a mystery to me"), whereas other items of the RFQ-R-7 show similar characteristics to rumination and worry (e.g., the item of "Strong feelings often cloud my thinking").…”
Section: Discussionsupporting
confidence: 87%
“…For example, difficulties in emotion regulation and mentalizing are overlapping constructs to some degree (e.g., the ability to understand emotions is considered in both emotion regulation and mentalization processes) and show neurobiological-level functional relationships. Therefore, previous studies consistently showed positive associations between difficulties in emotion regulation, maladaptive emotion regulation strategies and impairments in reflective functioning in clinical and non-clinical samples [2,[10][11][12][13][14]. In addition to this, some studies also reported positive correlations between impulsivity and mentalization difficulties which also can be explained by the similarities between these constructs (e.g., negative urgency-related characteristics, lack of premeditation can be considered as a form of reflective functioning difficulties) [10,11,15].…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, the Cronbach’s alpha reliability of RFQu subscale was slightly lower than 0.70. Even though this finding is quite consistent with similar research (Badoud et al, 2015; Vahidi et al, 2021), critical evaluations of RFQ raises some questions about the robustness of this questionnaire to measure two dimensions of hyper and hypomentalizing (Euler et al, 2021). We preferred to use RFQ for its research utility in relatively large samples.…”
Section: Discussionsupporting
confidence: 85%
“…The mentalizing view of the self and others subsequently allows someone to regulate affect (Fonagy et al, 1998(Fonagy et al, , 2016Schwarzer et al, 2021) as both mentalizing and affect regulation capacities are developmental achievements, rooted in early attachment relationships. Supportive research indicated links between mentalizing, emotion regulation, and BPD (Herpertz et al, 2018;Sharp et al, 2011Sharp et al, , 2013Vahidi et al, 2021). Our findings are in line with these theoretical postulations and empirical findings in that adolescents who lacked a functional degree of reflective stance towards the mental states of the self and others were more likely to experience difficulty in regulating their emotions, and subsequently to suffer from BPD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation